WASP-128b: a transiting brown dwarf in the dynamical-tide regime. Issue 4 (14th September 2018) - Hodžić, Vedad; Triaud, Amaury H M J; Anderson, David R; Bouchy, François; Cameron, Andrew Collier; Delrez, Laetitia; Gillon, Michaël; Hellier, Coel; Jehin, Emmanuël; Lendl, Monika; Maxted, Pierre F L; Pepe, Francesco; et al.
ABSTRACT: Massive companions in close orbits around G dwarfs are thought to undergo rapid orbital decay due to runaway tidal dissipation. We report here the discovery of WASP-128b, a brown dwarf discovered by the WASP survey transiting a G0V host on a $2.2\, d$ orbit, where the measured stellar rotation rate places the companion in a regime where tidal interaction is dominated by dynamical tides. Under the assumption of dynamical equilibrium, we derive a value of the stellar tidal quality factor $\log {Q_\star ^{′ }} = 6.96 ± 0.19$ . A combined analysis of ground-based photometry and high-resolution spectroscopy reveals a mass and radius of the host, $M_\star = 1.16± 0.04\, M_{\odot }$, $R_\star = 1.16± 0.02\, R_{\odot }$, and for the companion, $M_b = 37.5± 0.8\, M_J$, $R_b = 0.94± 0.02\, R_J$, placing WASP-128b in the driest parts of the brown dwarf desert, and suggesting a mild inflation for its age. We estimate a remaining lifetime for WASP-128b similar to that of some ultra-short period massive hot Jupiters, and note it may be a propitious candidate for measuring orbital decay and testing tidal theories.